Industrial organisation of the food industry in Latvia: results of an expert survey in the dairy and milling branches - Danute Jasjko (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 1999)
Based on the analytical framework of the structure-conduct-performance paradigm of the theory of industrial organisation, the paper analyses those economic conditions that determine the degree of competitiveness in the Latvian dairy and milling industry. The analysis is based on information from milk and grain processing enterprises acquired through a survey carried out at the beginning of 1998. It is shown that the development of market conditions and market behaviour in the sectors examined has in general progressed. Privatisation in both sectors has been completed. While in the dairy sector the majority of processing enterprises were privatised as co-operatives, in the milling industry all enterprises have become closed joint-stock companies. Since the legal status of a co-operative has turned out to be quite problematic for enterprise restructuring, more and more dairy enterprises have started to change into joint-stock companies. Competition in the investigated processing sectors can be considered as functioning. However, in the dairy sector tendencies of stronger horizontal concentration can be observed. The majority of enterprises react in quite an active way to the market conditions. Procurement and marketing channels have been diversified, and considerable investments have been undertaken. Further investments, however, are impeded by high interest rates for credits. As for performance, quite a considerable differentiation between the enterprises in the considered branches could be shown. The main problems seen by the processors are the saturation of the domestic Latvian market, the lack of investment funds, the unstable legislation, the absence of any substantial support from the government, and, in the dairy sector, the low quality of the raw milk. – – Der Diskussionsbeitrag analysiert mit Hilfe des Structure-Conduct-Performance Ansatzes der Industrieökonomik die Faktoren, die die Wettbewerbsfähigkeit der lettischen Milch- und Mühlenindustrie beeinflussen. Der Untersuchung liegen Informationen zugrunde, die im Rahmen einer Unternehmensbefragung Anfang 1998 gesammelt wurden. Es wird gezeigt, dass bei der Entwicklung marktwirtschaftlicher Rahmenbedingungen und Verhaltensweisen insgesamt beträchtliche Fort-schritte erzielt worden sind. Die Privatisierung ist in beiden Sektoren fast abgeschlossen. Während dabei im Milchsektor die meisten Betriebe als Genossenschaften privatisiert worden sind, haben alle Betriebe der Mühlenindustrie die Rechtsform einer geschlossenen Aktiengesellschaft angenommen. Da sich aber Genossenschaften als problematisch für die Unternehmensumstrukturierung erwiesen haben, sind mehr und mehr Milchverarbeitungsbetriebe dazu übergegangen, sich in Aktien-gesellschaften umzuwandeln. Der Wettbewerb in den untersuchten Sektoren kann als funktionsfähig bezeichnet werden. Allerdings ist in der Milchindustrie eine zunehmende horizontale Konzentration zu beobachten. Die meisten Betriebe reagieren recht aktiv auf die veränderten marktwirtschaftlichen Rahmenbedingungen. Die Beschaffungs- und Absatzkanäle wurden diversifiziert und es wurden beträchtliche Investitionen getätigt. Weitere Investitionen werden jedoch durch hohe Kreditzinsen behindert. Die Analyse der Leistungsfähigkeit zeigt, dass eine erhebliche Differenzierung zwischen den einzelnen Betrieben in den beiden untersuchten Branchen stattgefunden hat. Als Hauptprobleme der Verarbeitungsbetriebe werden die Sättigung des heimischen Marktes, fehlendes Kapital für Investitionen, eine unsichere Rechtslage und eine fehlende substantielle staatliche Unterstützung betrachtet. Für die Milchindustrie ist darüber hinaus die schlechte Qualität der Rohmilch ein großes Problem.
urn:nbn:de:gbv:3:2-22878
Keywords: 330; Milchverarbeitung; Zuckerindustrie; Struktur-Performance-Modell; Lettland